Analisis Ketepatan Kode Diagnosis Hipertensi Berdasarkan ICD-10 di Puskesmas Sukamulya - Nisa Umami; Nourma Nurjanah; Nova Oktavia; teguh tri sutarno (Jurnal Vokasi Kesehatan, 2025)
ICD-10 is an international disease classification system used for accurate and systematic diagnosis recording. Hypertension is one of the most prevalent diseases in primary health care facilities, including the Sukamulya Community Health Center. However, inaccuracies in diagnosis coding that do not comply with ICD-10 guidelines are still frequently found. This study aims to analyze the accuracy of hypertension diagnosis codes, describe the coding procedures, and identify factors affecting coding inaccuracies. This research employed a qualitative descriptive method with data collection through observation of 100 hypertension medical records and interviews with two coding officers. The results showed that 42% of diagnosis codes were accurate, while 58% were inaccurate. The inaccuracies were caused by limited understanding of combination codes, lack of coding training, and the absence of specific Standard Operating Procedures (SOPs). The study concludes that improving coding accuracy requires regular training and the development of clear SOPs.